2020
DOI: 10.1083/jcb.201809020
|View full text |Cite
|
Sign up to set email alerts
|

Rab18 regulates focal adhesion dynamics by interacting with kinectin-1 at the endoplasmic reticulum

Abstract: The members of the Rab family of small GTPases are molecular switches that regulate distinct steps in different membrane traffic pathways. In addition to this canonical function, Rabs can play a role in other processes, such as cell adhesion and motility. Here, we reveal the role of the small GTPase Rab18 as a positive regulator of directional migration in chemotaxis, and the underlying mechanism. We show that knockdown of Rab18 reduces the size of focal adhesions (FAs) and influences their dynamics. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Kinectin was identified using a function-blocking monoclonal antibody [196] and binds to the KIF5 C-terminus [197]. Kinectin has been implicated in the regulation of focal adhesion dynamics during chemotaxis by promoting ER targeting to focal adhesions at the cell's leading edge [198,199]. Interestingly, Rab18 is required for this process and forms a ternary complex with kinectin and kinesin-1 [198].…”
Section: Microtubule Motors Drive Er Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinectin was identified using a function-blocking monoclonal antibody [196] and binds to the KIF5 C-terminus [197]. Kinectin has been implicated in the regulation of focal adhesion dynamics during chemotaxis by promoting ER targeting to focal adhesions at the cell's leading edge [198,199]. Interestingly, Rab18 is required for this process and forms a ternary complex with kinectin and kinesin-1 [198].…”
Section: Microtubule Motors Drive Er Dynamicsmentioning
confidence: 99%
“…Rab18 is involved in several ER-related processes including the regulation of ER-lipid droplet MCS involving the NRZ complex and SNARE proteins [343,360] (but not under all conditions [8]) and the maintenance of normal ER morphology [8]. As described in Section 3.1.1, Rab18 has also recently been shown to promote anterograde ER tubule transport via its interaction with kinectin-1 [198] and in agreement with this result, the dynamic tubular regions of the network were absent in cells depleted of Rab18 [8]. A similar relationship between morphology-regulating proteins, ER dynamics and disease is observed with ataxin-2 in spinocerebellar ataxia type 2 (SCA2).…”
Section: Disease Protein Implicated Protein Role In Healthy Er Function Affected In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several Rab proteins, including Rab8, Rab6, and Rab7b, can indeed influence cytoskeleton dynamics by modulating the activity of members of the Rho family of small GTPases ( Borg et al., 2014 ; Bravo-Cordero et al., 2016 ; Kjos et al., 2018 ; Vestre et al., 2019 ). Other Rabs take part in integrin recycling ( Sahgal et al., 2019 ; Wang et al., 2010 ) or in focal adhesion turnover ( Guadagno et al., 2020 ; Mendoza et al., 2013 ). Given the involvement of these small GTPases in cell motility, it is not surprising that their abnormal regulation is often associated with migratory ability and invasiveness in different types of cancer ( Diaz et al., 2014 ; Guadagno and Progida, 2019 ; von Thun et al., 2012 ; Wang et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hanry Yu’s lab first demonstrated that KTN1 interacts with elongation factor-1δ (EF-1δ) to anchor the EF-1δ complex in the ER, while it also increases the synthesis of membrane or secretory proteins [ 26 ]. Additionally, Cinzia Progida’s lab demonstrated that Rab18 directly interacts with KTN1 to anchor the ER via kinesin-KTN1 for focal adhesion (FA) growth and dynamics [ 27 ]. KTN1 has been shown to directly bind kinesin, and a current research focus involves identifying inhibitors of kinesin spindle protein (KSP) as targets for multi-cancer therapy [ 28 ].…”
Section: Introductionmentioning
confidence: 99%